First Report on Ecology of Vattakkayal, Kollam, Kerala - Neethu G. P; Sruthi. S; Anzeer.F. M and Tresa Radhakrishnan (IJSR - INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH, 2014)
Hydrobiological parameters of Vattakkayal of Kavanad, Kollam District, Kerala was carried out and the results are included in this paper. Survey was undertaken and five stations were fixed from where monthly samples for physiochemical parameters were collected during the period from November-2013 to July-2014. Vattakkayal is the life line of the people Maruthady and Sakthikulangara, it should be protected from further damage and destruction. The kayal is already facing with a lot of prob- lems both ecologically and topographically it is high time that this water body should be rejuvenated and remedial measures should be taken to protect it for further havoc. Urgent steps should be taken in order to bring back this ecosystem from its present stage. In order to protect this precious water body from further deteriorations immediate attention should be give on the following aspects such as, by enforcing stringent rules and regulations, by preventing dumping of municipal solid and sewage wastes and industrial wastes into the lake, by preventing the light fishing and mass destruction of juveniles, fries and fingerlings by way of mesh size regulation, by recovering the encroached area and prevent further encroachment into the lake and also by creating an awareness among the public about the importance of Vattakkayal and its terrain from further degeneration, destruction, deterioration and death.